2010
DOI: 10.1002/jrs.2775
|View full text |Cite
|
Sign up to set email alerts
|

Raman and SERS study on cimetidine–metal complexes with biomedical interest

Abstract: Cimetidine (cim) is one of the most potent histamine H 2 -receptor antagonists for inhibiting excessive acid secretion caused by histamine; it has been hypothesized that the therapeutic effects can be related to its interactions with metal ions. Raman spectra of the solid cim with Co(II), Cu(II), Ni(II) and Zn(II) metal complexes show that they can adopt two different structures: one is octahedral and the other, with Zn(II), is probably tetrahedral. The octahedral structure appears to be distorted both by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…shows three bands at 9324, 14431 and 24964 cm -1 assigned to the 3 Table 1.Selected stretching vibrations (cm -1 ) for cimetidine and complexes 1-9.…”
Section: Ir and Electronic Absorption Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…shows three bands at 9324, 14431 and 24964 cm -1 assigned to the 3 Table 1.Selected stretching vibrations (cm -1 ) for cimetidine and complexes 1-9.…”
Section: Ir and Electronic Absorption Spectramentioning
confidence: 99%
“…Cimetidine, (scheme 1), 2-cyano-1-methyl-3-(2-[(5-methyl-1H-imidazol-4-yl)-methyl-thio]-ethyl)-guanidine, is a potent histamine H 2 -receptor antagonist, which inhibits excessive acid secretion caused by histamine, and is used for treatment of peptic ulcer [1]. This drug has the ability to chelate metal ions in blood plasma and in different tissues [2], and it had previously been suggested that the main therapeutic action of cimetidine might be mediated by its interactions with essential metal ions [3]. It resulted interesting to find out whether cimetidine could compete for Cu II ion against biological ligands such as albumin [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonora and co‐workers used SERS to analyze the structures of Cimetidine (cim), one of the most potent histamine H2‐receptor antagonists for inhibiting excessive acid secretion caused by histamine, complexed with various metal ions, Co(II), Cu(II), Ni(II), and Zn(II), to understand the differences in therapeutic effects for these metals . The art conservation field has seized upon the opportunity opened up by the power of SERS to enable the identification of microscopic amounts of organic molecules used as artists' colorants in complex matrixes, such as biomaterials.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…This drug has the ability to chelate metal ion in blood plasma and in different tissue 12 . and it had previously been suggested that the main therapeutic action of cimetidine might be mediated by its interaction with essential metal ions. 13,14 …”
Section: Introductionmentioning
confidence: 99%